Entrapping method surface modification for preparation of membrane adsorber - Mohd. Yusof, Abdul Halim; Ulbricht, Mathias (2006)
Ion-exchange chromatography in packing bed is one of techniques widely used in the purification of protein. However, this technique has some limitations such as intraparticle diffusion of solute transport, high pressure drop; radial and axial dispersion limitation and chanelling. These factors make scale up of packed bed chromatographic processes difficult. Recently, membrane adsorber has been introduced as an alternative to overcome these problems. In this work, surface modification with UV irradiation using photoinitiator entrapping method was used to produce membrane adsorber. This is based on the simplicity and the economic value of such method [1,2]. Polypropylene microporous membrane was used as substrate, benzophenone was used as photoititiator in different range of concentration (0.01-1 wt %) and Acrylic acid (AA); Acrylamide (AAm) and N,N'-methylenebisacrylamide (MBAA) were used as monomer in different mixture of composition. Degree of grafting, permeability, ATR-FTIR, and protein reversible binding were used as methods of evaluation. Membrane adsorber produced with photoinitiator 0.1wt% yielded optimum degree of grafting and combination of Acrylic acid and low amount N,N'-methylenebisacrylamide showed highest protein reversible binding. The overall results showed variations of photoinitiator concentration and monomer composition had significant influence on membrane adsorber performance.